ibM Kelompok Tani Jamur Tiram di Kelurahan Tlogomulyo - Fatmasari Sukesti; Setia Iriyanto; Purnomo Purnomo (Universitas Muhammadiyah Semarang, 2014)
Oyster mushrooms easily to cultivated so this activities become to choice of small and medium enterprises (SMEs) to conduct cultivation. Oyster mushroom (Pleurotus ostreatus) is a nutritious food ingredients with high protein, rich in vitamins and minerals, low in carbohydrates, fat and calories. Oyster mushroom products can not only be consumed in the form of cooked vagetables, but can be processes into a form processed foods like crispy mushrooms, mushroom chips, nuggets mushroom, mushroom dumplings, and other processed foods. Farmer groups